Sexual and Reproductive Health for Women Who Live With Inflammatory Bowel Disease: An Integrative Review - Kate O'Reilly; Susan McInnes; Eleanor Holroyd; Kath Peters (Nursing Open)
ABSTRACT Aims To provide an understanding of the sexual and reproductive health issues for women who live with inflammatory bowel disease. Design Whittemore and Knaffle's integrative review. Methods Databases searched in this integrative review included: CINAHL Plus, Google Scholar, SCOPUS and Web of Science databases. A defined research aim guided the search strategy and facilitated the accurate extraction of data from primary qualitative and quantitative research conducted between 2012 and 2022. Results Nineteen papers were included in this review. All papers were appraised using the Mixed Methods Appraisal Tool and were found to be of good methodological quality. The following three themes were identified: (1) inflammatory bowel disease negatively impacts sexual, reproductive and social health; (2) inflammatory bowel disease and sexual functioning and (3) reproductive knowledge and reservedness to discuss sexual health. This review of the literature highlights that sexual and reproductive health issues for women who live with inflammatory bowel disease are very focused on sexual dysfunction and reproduction. The review illuminates that there is a dearth of information that explores women's sexuality more broadly across the lifespan.